Tanggapan Masyarakat Semarang Tengah Terhadap Potensi Roti Gandjelrel Sebagai Kuliner Di Luar Masa Dugderan - Sutandi, Tiara Regina; Chrisyanti Dewi, Irra (Universitas Pahlawan Tuanku Tambusai, 2024)
This research aims to explore the distinctive characteristics of two variants of kokot broth in Sumenep and Pamekasan. Qualitative methods were used to analyze the taste, aroma and texture of kokot broth through interviews with sellers and consumers. Informants were selected through purposive sampling of 10 people and 2 kokot broth sellers in Pamekasan and Sumenep. The results highlighted significant differences between the characteristics of coco stock from the two regions. Based on the taste analysis, in Pamekasan it is savory, it has fried onions and in Sumenep it is savory, it has fried onions and there is peanut sauce on top. The texture of the cocoa beans from both regions is very soft, easy to eat and has no smell. Based on the aroma, in Pamekasan it is fragrant and smells slightly of ginger and in Sumenep it is fragrant and smells of peanut sauce. The color of the kokot in Pamekasan is clear and in Sumenep it is cloudy. Apart from that, the habit of buying kokot broth in Pamekasan and Sumenep is that they only eat one portion on the spot and wrap it in more than one portion according to their wishes. The frequency of purchasing kokot broth in Pamekasan is sometimes once a month or more and in Sumenep once a month or two months or more than twice a month depending on consumer desires. In addition, this research reveals people's preferences for one variant of kokot broth which reflects the culinary and cultural uniqueness of Sumenep or Pamekasan. These findings have important implications for further understanding regional culinary diversity in Indonesia, especially on Madura Island, and provide valuable insights for the development of local food products.